104k views
0 votes
Rewrite the function by completing the square. h(x)=2x^2+11x+15


h(x)=__(x+__)^2+__

User Heymega
by
5.0k points

2 Answers

1 vote

Answer:

h(x)+2(x+11/4)^2+-1/8

Explanation:

User Arielnmz
by
6.1k points
2 votes

Hello,


h(x) = 2x^2+11x+15

we can notice that


(x+(11)/(4))^2 = x^2+(11)/(2)x+{((11)/(4))}^2

so we can write


2x^2+11x = 2 [ {(x+(11)/(4))^2-{((11)/(4))}^2 ]

then it comes


h(x) = 2 [ {(x+(11)/(4))^2-{((11)/(4))}^2 ] + 15\\= 2 {(x+(11)/(4))^2 +15-{(11^2)/(8)}\\= 2 {(x+(11)/(4))^2 +{(15*8-11^2)/(8)}so


h(x) = 2{(x+(11)/(4))^2-{(1)/(8)}

User MisterZimbu
by
5.9k points